아황산나트륨을 이용한 스프링클러 동배관 공식 부식 방지 - 서상희; 서영준; 권혁상 (한국부식방식학회, 2017)
Inhibition of pitting corrosion of the copper sprinkler tubes by removing dissolved oxygen in water withsodium sulfite was studied on the wet sprinkler systems operated in 258 household sites. First, air in thesprinkler tubing was removed by vacuum pumping. The tube was then filled with sodium sulfite dissolvedin water. Sodium sulfite was very effective in maintaining a very low dissolved oxygen concentration inwater in the sprinkler tube for the observation period of six months. Water leakage from the copper sprinklertube was reduced significantly by using sodium sulfite. Both pitting corrosion process and pitting corrosioninhibition mechanism were investigated by examining microscopical and structural aspects of corrosion pitsformed in failed copper sprinkler tube. Pitting corrosion was caused by pressurized air as well as sedimentssuch as sand particles in copper tubes through oxygen concentration cells. It was confirmed microscopicallythat growth of corrosion pits was stopped by reducing dissolved oxygen concentration to a very level byusing sodium sulfite.